Characterization of a Novel Hot-Spring Cyanobacterium Leptodesmis sichuanensis sp. Nov. and Genomic Insights of Molecular Adaptations Into Its Habitat - Tang, Jie; Du, Lian-Ming; Li, Meijin; Yao, Dan; Jiang, Ying; Waleron, Malgorzata; Waleron, Krzysztof; Daroch, Maurycy (Frontiers in Microbiology, 2022)
The newly described genus Leptodesmis is filamentous cyanobacteria that comprises strains from diverse, primary cold, habitats. Here, we sequenced the complete genome of a novel hot-spring strain, Leptodesmis sp. PKUAC-SCTA121 (hereafter A121), isolated from Erdaoqiao hot springs (pH 6.32, 40.8oC), China. The analyses of 16S rRNA/16S-23S ITS phylogenies, secondary structures and morphology strongly supported strain A121 as a new species within Leptodesmis, Leptodesmis sichuanensis sp. nov. Notably, strain A121 is the first thermophilic representative of genus Leptodesmis and more broadly the first Leptodesmis sp. to have its genome sequenced. In addition, results of genome-scale phylogenetic analysis and average nucleotide/amino acid identity as well as in silico DNA-DNA hybridization and patristic analysis verified the establishment of genus Leptodesmis previously cryptic to Phormidesmis. Comparative genomic analyses revealed that the Leptodesmis A121 and Thermoleptolyngbya sichuanensis A183 from the same hot-spring biome exhibited different genome structures but similar functional classifications of protein-coding genes. Although the core molecular components of photosynthesis, metabolism, and signal transduction were shared by the two strains, distinct genes were also noticed to be associated with photosynthesis, signal transduction, etc., indicating that different strategies might be used by these strains to adapt to that specific niche. Furthermore, the complete genome of strain A121 provides the first insight into the genomic feature of genus Leptodesmis and lays the foundation for future global ecogenomics and geogenomic studies.